SYNTHESIS OF SILVER NANOPARTICLES FROM THE TOTAL EXTRACT OF YETMAK (ACANTHOPHYLLUM GYPSOPHILOIDES) (Global Conference on Multidisciplinary Research and Innovation, 2026)
In this study, it was aimed to isolate silver nanoparticles from the extract of Allochrusa gypsophiloides (Yetmak) plant. This work is carried out based on the green synthesis method. The green synthesis method is considered an environmentally friendly and safe method. Today, due to the rapid development of the fields of nanobiotechnology and nanomedicine, interest in nanosized materials is sharply increasing. In particular, silver nanoparticles (AgNPs) are at the center of scientific research due to their physicochemical and biological properties. Their high surface area, optical properties, chemical stability, and biological activity are widely used in various fields, particularly in medicine, pharmaceuticals, and biotechnology.
Keywords: Allochrusa gypsophiloides (Yetmak), green synthesis, silver nanoparticles, flavonoids, saponins.